How to enjoy art a guide for everyone - Street, Ben 1978- (New Haven Yale University Press, 2021)
"How to Enjoy Art : A Guide for Everyone' provides the tools to understand and enjoy works of art. Debunking the pervasive idea that specialist knowledge is required to understand and appreciate art, instead How to Enjoy Art focuses on experience and pleasure, demonstrating how anyone can find value and enjoyment in art. Examples from around the world and throughout art history-from works by Fra Angelico and Berthe Morisot to Kazuo Shiraga and Kara Walker-are used to demonstrate how a handful of core strategies and skills can help enhance the experience of viewing art works. With these skills, anyone can encounter any work of art-regardless of media, artist or period-and find some resonance with their own experiences. How to Enjoy Art encourages us to rediscover the fundamental pleasure in viewing art."--Dust jacket flap.
Includes bibliographical references.
Keywords: Art appreciation; Art criticism; Art, Modern -- 21st century